Road to Success: How does entrepreneurial orientation and market orientation improve SME performance? - Rahmawati, Rizqi; Catur Sudyantara, Smita; Almas, Nauva; Hasyim Sholeh, Mohammad (El-Barka, 2024)
SMEs are one of the pillars of the economy that continues to move daily in carrying out its business activities. Each business field has different characteristics, but striving to develop a business and earn income is one of the main capitals to continue to advance. There are so many obstacles faced by MSME players to compete in the market so the management of business breakthroughs is important to support business development. Maintaining a business existence requires a strong entrepreneurial spirit so that it can achieve the desired business goals. Also, market orientation and entrepreneurship could positively impact SMEs' performance. In this study, it is explained that innovation also plays an important role in improving the performance of SMEs. A conceptual structural model that includes aspects of Market Orientation (MO), entrepreneurial orientation (EO), Innovation (I), and SME Performance (SMEP) is developed based on the concept and relationship results from the literature. This study examines the influence of entrepreneurial and market orientation on whether it has a direct or indirect impact on SME performance. This study investigates whether entrepreneurial orientation and market orientation affect the performance of SMEs using innovation mediation. The population of this study is Small and Medium Enterprises (SMEs) in the city of Pacitan, East Java engaged in food and beverages, services, and production, with a sample of 100 SMEs. In research using Structural Equation Modeling (SEM) analysis tools. and it is expected that this research will have an impact on SMEs in the city of Pacitan, which focuses on how entrepreneurial orientation and market orientation have an impact on SME performance, both directly and indirectly, and how Innovation as a mediating variable can have a direct or indirect impact on entrepreneurial orientation and market orientation on SME performance.